Innovative Forms of Production Organization in the Context of High-Tech Meso-Economic Systems Sustainable Development - Alexey I. Shinkevich; Alsu A. Lubnina; Natalia M. Chikisheva; Lyudmila M. Simonova; Elena E. Alenina; Boris B. Khrustalev; Roza Sh. Sadykova; Regina R. Kharisova (International Review of Management and Marketing, 2016)
The article’s objectives involve the models’ development to stimulate joint innovation activities of enterprises of chemistry and technology of polymeric and composite materials based on new forms of co-competition relationships. The leading method to the problem study is a simulation method that allows this issue’s consideration as a focused and organized process to improve the innovative development management of industrial enterprises of chemistry and technology of polymeric and composite materials based on the co-competition model. The article suggests the co-competition classification, which is adequate to various types of innovative projects; a set of recommendations on the appropriateness of co-competition models’ choice for enterprises of chemistry and technology of polymeric and composite materials is scientifically justified. The practical value is that the developed techniques allow at a greater expense and more concretely to regulate innovative activity of enterprises through the co-competition models’ use and can be used in the framework of industrial programs.